2019
DOI: 10.1111/bjd.18369
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin safety in infants and children under 15 kg treated for scabies: a multicentric observational study

Abstract: Summary Background Scabies is a frequent condition seen in infants and children. Only topical treatments have been approved in infants, but some of them are poorly tolerated. Oral ivermectin is approved for the treatment of scabies in several countries, but its use in infants and children weighing < 15 kg is off label. Objectives To assess the safety of ivermectin in infants and young children, and to collect data on ivermectin efficacy in these age groups. Methods This study was performed in the dermatology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
64
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 15 publications
2
64
0
5
Order By: Relevance
“…Topical permethrin and systemic/topical ivermectin are ‘broad-spectrum’ compounds of choice [ 11 ]. However, permethrin is not recommended for use in infants, and ivermectin is contra-indicated in patients with severely impaired liver or kidney function and the safety of its use in pregnant women and in children of < 15 kg body weight is only beginning to be investigated [ 12 , 13 ]. Some other agents, such as sulphur, crotamiton, malathion and benzyl benzoate are presently available for topical application in children, but their clinical efficacies and tolerability have not been adequately assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Topical permethrin and systemic/topical ivermectin are ‘broad-spectrum’ compounds of choice [ 11 ]. However, permethrin is not recommended for use in infants, and ivermectin is contra-indicated in patients with severely impaired liver or kidney function and the safety of its use in pregnant women and in children of < 15 kg body weight is only beginning to be investigated [ 12 , 13 ]. Some other agents, such as sulphur, crotamiton, malathion and benzyl benzoate are presently available for topical application in children, but their clinical efficacies and tolerability have not been adequately assessed.…”
Section: Introductionmentioning
confidence: 99%
“…In reply : We thank Morton and Morton for summarising the international evidence for the safety of ivermectin in children and pregnancy. We agree that there is accumulating evidence that ivermectin is likely to be safe in small children and pregnancy . However, currently in Australia, ivermectin is only licensed for use in children aged over 5 years and weighing more than 15 kg and when treatment with first line scabicides has failed or is contraindicated.…”
mentioning
confidence: 84%
“…Australian guidelines state ivermectin should not be used in children aged under 5 years or who weigh less than 15 kg or in pregnant women . A retrospective cohort study of 170 children aged 1–64 months (median age, 15 months) or weighing under 15 kg treated with ivermectin (mean dose, 223 μg/kg) found only minor self‐limiting adverse effects in seven patients (4%) . A review of previous literature found 60 children aged under 5 years or weighing less than 15 kg who had been treated with ivermectin at a dose range of 150–200 μg/kg for whom safety data were available .…”
mentioning
confidence: 99%